Development and underground test of radiopure ZnMoO4scintillating bolometers for the LUMINEU 0$\upnu$2$\upbeta$ project - Armengaud, Eric; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana (Journal of Instrumentation, 2015)
The LUMINEU (Luminescent Underground Molybdenum Investigation for NEUtrino mass and nature) project envisages a high-sensitivity search for neutrinoless double beta (0ν 2β) decay of 100Mo with the help of scintillating bolometers based on zinc molybdate (ZnMoO4) crystals. One of the crucial points for the successful performance of this experiment is the development of a protocol for producing high quality large mass ZnMoO4 crystal scintillators with extremely high internal radiopurity. Here we report a significant progress in the development of large volume ZnMoO4 crystalline boules (with mass up to 1 kg) from deeply purified materials. We present and discuss the results achieved with two ZnMoO4 samples (with mass of about 0.3 kg each): one is a precursor of the LUMINEU project, while the other one was produced in the framework of LUMINEU with an improved purification / crystallization procedure. The two crystals were measured deep underground as scintillating bolometers in the EDELWEISS dilution refrigerator at the Laboratoire Souterrain de Modane (France) protected by a rock overburden corresponding to 4800 m w.e. The results indicate that both tested crystals are highly radiopure. However, the advanced LUMINEU sample shows a clear improvement with respect to the precursor, exhibiting only a trace internal contamination related with 210Po at the level of 1 mBq/kg, while the activity of 226Ra and 228Th is below 0.005 mBq/kg. This demonstrates that the LUMINEU purification and crystal-growth procedures are very efficient and leads to radiopurity levels which exceedingly satisfy not only the LUMINEU goals but also the requirements of a next-generation 0ν 2β experiment.
Gesehen am 28.07.2020